Student workload assessment for online learning: An empirical analysis during Covid-19. Issue 1 (1st January 2022) - Therisa Beena, Karingada Kochu; Sony, Michael
Abstract: Covid-19 has forced most educational institutions around the world to migrate to online learning in an emergency mode to protect students from the pandemic. This sudden migration to online learning has created multi-dimensional demands on students. Therefore, student workload needs to be measured during online learning. The purpose of this study is to measure the student workload from student perception by evaluating online learning in terms of Mental demand (MD), Physical demand (PD), Temporal demand (TD), Effort (EF), Performance (PE) and Frustration (FR). This study through a cross-sectional survey analysed 223 student's workloads on six dimensions using a NASA -TLX scale. The study finds all six components of workload significant for student assessment during online learning. Besides, the NASA-TLX scale was tested using confirmatory factor analysis for its ability to assess student workload for online learning. This is the first study to assess the student workload for online learning and hence contributes to the theory of measurement of workload assessment for online learning. The educational institutions can use this study to measure the student workload assessment for various courses offered by them using this simple tool.